2020
DOI: 10.1097/meg.0000000000001835
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of high-dose dual therapy, bismuth-based quadruple therapy and non-bismuth quadruple therapies for Helicobacter pylori infection: a network meta-analysis

Abstract: Helicobacter pylori (H. pylori) infection is associated with the development of multiple diseases. The eradication rate of H. pylori has gradually decreased, suggesting the need to discover more effective therapies. This study aimed to compare the effectiveness of first-line treatments including high-dose dual therapy (HDDT), bismuth-based quadruple therapy (BQT), sequential therapy (ST), concomitant therapy (CT) and hybrid therapy (HT) by network meta-analysis (NMA). A comprehensive search on PubMed, Embase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Two network meta-analyses also explored the eradication rates of different first-line treatment regimens [ 19 , 27 ]. One of them included 41 RCTs comparing mainly concomitant and sequential therapy but also reverse hybrid therapy, as well as different bismuth-based quadruple therapies, where five studies included a HDDT arm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two network meta-analyses also explored the eradication rates of different first-line treatment regimens [ 19 , 27 ]. One of them included 41 RCTs comparing mainly concomitant and sequential therapy but also reverse hybrid therapy, as well as different bismuth-based quadruple therapies, where five studies included a HDDT arm.…”
Section: Discussionmentioning
confidence: 99%
“…One of them included 41 RCTs comparing mainly concomitant and sequential therapy but also reverse hybrid therapy, as well as different bismuth-based quadruple therapies, where five studies included a HDDT arm. The results of this meta-analysis suggested that 14-day HDDT was the preferred first-line treatment in the Asian population [ 27 ]. Another network meta-analysis (68 studies, three of them with an HDDT arm) showed that HDDT was more effective than bismuth-based triple and quadruple therapies but less effective than non-bismuth concomitant, sequential, and reverse hybrid quadruple treatments, levofloxacin-containing therapy, and vonoprazan-triple therapy [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another meta-analysis (2020), HDDT was equivalent to the recommended first-line or rescue regimens (triple therapy, BCQT, and non-bismuth quadruple therapy) with fewer side effects [ 42 ]. Similarly, by a network meta-analysis (2021), HDDT for 14 days appeared to be the most optimal primary therapy for H. pylori among Asian populations with comparable efficacy and compliance and causing fewer side effects [ 43 ].…”
Section: F Uture Hope: Roles Of Bismuth Compound and Vonopr...mentioning
confidence: 99%